E-Commerce and Insurance Internet Marketing: A Business Review from Indian Context (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper deals the conceptual knowledge of search engine marketing (SEM) or e-commerce, literature review, current and future aspects of e-commerce in Indian context. This paper discussed about the top motivator factors of shopping online. The present development would be a valuable addition to researcher and academicians; and useful theory for practitioners, advertisers, and entrepreneurs